Cervical Cancer During the COVID-19 Pandemic in Rural Communities of Ayacucho: Cáncer de cérvico uterino en la pandemia de COVID-19 en comunidades rurales de Ayacucho | 在COVID-19大流行期间，秘鲁Ayacucho农村社区的宫颈癌 - Orellana de Piscoya, Lucy (2024)
Introduction: Due to the COVID-19 pandemic, vulnerable rural women faced significant challenges. Objective: To explore the situation of cervical cancer during the pandemic from an intercultural perspective among rural women in Ayacucho in 2021. Methodology: Mixed-method research with a concurrent triangulation design. Sample: Healthcare providers and rural women. Purposeful and reasoned sampling. Techniques: Surveys, in-depth interviews. Data analysis: Data systematization using Excel, SPSS for quantitative data, and Atlas.ti for qualitative data. Level of validity and confidence: triangulation.Results: Information from surveys and interviews was contrasted, revealing that the problem may have alternative solutions within the knowledge of the same communities.Conclusion: Women reported lack of awareness, insufficient information in the Quechua language, and undervaluation of their traditional knowledge. Fear and contagion concerns prevented them from seeking healthcare services. Services were reduced, redirected, or discontinued, often due to budget constraints.